Symptomatic Urinary Lithiasis: Epidemiology and Management at Urology Department of University Hospital of Cotonou - HOUNNASSO, PRINCE PASCAL; AVAKOUDJO, JOSUÉ DEJINNIN GEORGES; PARE, A.; KIRAKOYA, BRAHIMA; OUATTARA, A.; AGOUNKPE, M. M.; NATCHAGANDE, GILLES; TORE SANNI, R.; ABUBAKAR, Babagana Mustapha3; VODOUNOU, A. (My University, 2015)
Purpose: To study the epidemiology and treatment modalities of urolithiasis at Urology Department of University Hospital of Cotonou. Materials and Methods: It was a retrospective and descriptive study over a 10 years period ranging from January 1st, 2004 to December 31st, 2013. One hundred and two patients who were hospitalized for symptomatic urolithiasis at the Urology Department of University Hospital of Cotonou were enrolled. Results: Hospital incidence of urolithiasis was 3.7%. Patients mean age was 39.6 years (extremes: 10 years to 73 years). Male to female ratio was 2.2. The main reason for consultation was renal colic for 81 patients (79.4%). Average duration of symptoms at presentation was 5 months (range: 1 day to 10 years). A total of 173 stones were identified with an average size of 12 mm (range: 1 mm to 95 mm). Calyceal stones were seen in 32.9% of cases, renal pelvis stones in 21.4% of cases, ureteral stones in 34.1% and bladder stones in 11.5% of cases. Open surgery was the main treatment for stones that could not be managed medically. 50.8% of patients underwent surgery with extraction of 116 stones. This represented 67.1% of all stones. 9 patients (8.8%) had expelled their stone during urination. The postoperative course was uneventful in 77.5% of cases. Conclusion: Modern treatment options for urolithiasis remain rudimentary in our health facilities. Open surgery is still the main stay of treatment in our countries with limited resources.
Keywords: Urolithiasis; Renal Calculi; Bladder Calculi; Epidemiology; Open Surgery